User interface design guidelines for digital television virtual remote controls - Wentzel, Alicia Veronica (Rhodes University, Faculty of Commerce, Department of Information Systems, 2016)
The remote control is a pivotal component in households worldwide. It helps users enjoy leisurely television (TV) viewing. The remote control has various user interfaces that people interact with. For example, the physical user interface includes the shape of the remote and the physical buttons; the logical user interface refers to how the information is laid out; and the graphical user interface refers to the colours and aesthetic features of the remote control. All of the user interfaces together with the context of use, cultural factors, social factors, and prior experiences of the user influences the ways people interact with their remote control and ultimately has an effect on their user experiences. Advances in the broadcasting sector and transformations of the TV physical remote control have compounded the simple remote control into a multifaceted, indispensable device, overcrowded with buttons. The usability and ultimately the user experience of physical remote controls (PRCs) have been affected by the overloaded functionality and small button sizes. The usability issues with current PRCs, the evolution of mobile phones into touchscreen smartphones, and the trend of global companies moving towards virtual remote controls (VRCs) have prompted this research to discover what user interface design features will contribute towards an enhanced user experience for digital TV VRCs. This research used the design science research process model (DSRP), which comprised six steps, to investigate this topic area further. A review of the domain literature pertaining to mobile user experiences (MUX) and all the encompassing factors, mobile human computer interaction (MHCI) and the physical, logical, graphical and natural user interfaces was completed, as well as a review of the literature regarding the usability issues of PRCs and VRCs. A contextual task analysis (CTA) of a single South African digital TV PRC was used to identify how users utilise PRCs to perform tasks, and the usability issues they encountered during the tasks. Brainstorming focus groups were used to understand how to represent certain user interface elements and attempted to source ideas from users about what potential functionality digital TV VRCs should contain. Together with all the other results gathered from the previous chapters amalgamated into a set of user interface design guidelines for digital TV VRCs. The proposed user interface guidelines were used to instantiate a digital TV VRC prototype that underwent usability testing in order to validate the proposed user interface design guidelines. The results of the usability testing revealed that the user interface design guidelines for digital TV VRCs were successful, with the addition of one guideline that was discovered during the usability testing.
Keywords: Remote control; User interfaces (Computer systems); Television broadcasting; Human-computer interaction